Legal Protection for Medical Personnel in Providing Anesthesia Services to Patients Based on Health Laws - Fadli , Kartika Hariandiny; Dahlan, Dahlan (IHSA Institute, 2024)
Medical personnel providing anesthesia services often face legal challenges, as the outcomes of such procedures may lead to patient disability or death, raising concerns of malpractice from the patient’s family. While conducting their duties, medical personnel are entitled to legal protection, making it essential to examine this issue. This research, titled “Legal Protection of Medical Personnel in Providing Anesthesia Services to Patients Based on the Health Law,” addresses the following questions: 1) What are the legal regulations for medical personnel in anesthesia services? 2) What risks are involved? 3) How are medical personnel legally protected in anesthesia services?. Using normative juridical research and a statutory approach, this study analyzes existing regulations and secondary sources. Although Indonesia’s Health Law does not specifically address anesthesia, the Minister of Health Decree No. HK.01.07/MENKES/1541/2022 provides guidelines for anesthesiology and intensive care, given the high risks involved. To safeguard patient safety, medical personnel take preventive measures to minimize anesthesia risks. Since anesthesia is a high-risk procedure that may result in severe outcomes, including death, enhancing its categorization within the Health Law is crucial. Legal protection for medical personnel includes preventive measures, reducing the risk of legal consequences, and repressive measures, offering support if adverse events occur